Desensitization of TRPV1 Involved in the Antipruritic Effect of Osthole on Histamine-Induced Scratching Behavior in Mice. (13th October 2021) - Yang, Niuniu; Ju, Ying; Huang, Delun; Ling, Kunhong; Jin, Han; Liu, Jiamin; Ma, Jing; Chen, Yongxin; Zhang, Yingge; Zhu, Chan; Yang, Yan; Tang, Zongxiang; et al.
Abstract : Osthole has been isolated from the fruits of Cnidium monnieri (L.) Cusson, which has been used in Chinese traditional medicine to treat pruritic disorders for a long time. However, the antipruritic mechanism of osthole is not fully understood. In the present study, using calcium imaging, molecular docking, and animal scratching behavior, we analyzed the pharmacological effects of osthole on transient receptor potential vanilloid 1 (TRPV1). The results showed that osthole significantly induced calcium influx in a dose-dependent manner in dorsal root ganglion (DRG) neurons. Osthole-induced calcium influx was inhibited by AMG9810, an antagonist of TRPV1. Osthole and the TRPV1 agonist capsaicin-induced calcium influx were desensitized by pretreatment with osthole. Furthermore, molecular docking results showed that osthole could bind to TRPV1 with a hydrogen bond by anchoring to the amino acid residue ARG557 in the binding pocket of TRPV1. In addition, TRPV1 is a downstream ion channel for the histamine H1 and H4 receptors to transmit itch signals. Osthole attenuated scratching behavior induced by histamine, HTMT (histamine H1 receptor agonist), and VUF8430 (histamine H4 receptor agonist) in mice. These results suggest that osthole inhibition of histamine-dependent itch may be due to the activation and subsequent desensitization of TRPV1 in DRG neurons.